Signatures of substorm related overshielding electric field at equatorial latitudes under steady southward IMF Bz during main phase of magnetic storm. Issue 10 (15th November 2019) - Veenadhari, Bhaskara; Kikuchi, Takashi; Kumar, Sandeep; Tulasiram, S.; Chakrabarty, D.; Ebihara, Yusuke; Reeves, G.D.
Abstract: During the geomagnetic storm periods, the convection electric field penetrates promptly to equatorial latitudes, causing an eastward electric field in the dayside ionosphere. Occasionally, the polarity of the dayside ionospheric electric field is inverted when the Interplanetary Magnetic Field (IMF) turns northward. In this paper, interesting observations of the strong westward electric field in the day side equatorial latitudes are presented, as evidenced by strong Counter Electrojet (CEJ) at Indian and Japanese sectors under the steady southward IMF Bz. The westward electric field perturbations are quite large with CEJ amplitude of ∼−120 nT over the Indian sector (14–15 December 2006) and ∼−220 nT for Japanese sector (7–8 November 2004). The plausible mechanisms for the observed overshielding electric fields under steady southward IMF Bz have been investigated in light of the possible role of substorm activity. The clear signatures of substorm were observed at geosynchronous particle flux measurements from LANL (Los Alamos National Laboratory) satellite and associated with sudden decrease in AL index. The observed variations of asymmetric ring current shows the enhancement of Partial Ring Current (PRC) at the dusk sector further supporting the substorm onset during that period which will probably enhance the overshielding due to increased Region 2 Field-Aligned Currents (R2 FACs). The observations of such significantly large amplitudes of CEJ associated with the substorm related overshielding events are sparse and the results bring out the important role of substorm onset and the development of PRC in accordance with the R2 FACs during intense magnetic storms which alter the day time equatorial electric field perturbations.